Implementasi Bimbingan Kelompok Berbantuan Media Video untuk Mengurangi Kecemasan Menarche Remaja - Utami Fitri, Hartika; Putra, Bela Janare; Anggraini, Cici Lestari; Marianti, Lena; Makmum, Muh Ngali Zainal (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to determine the effectiveness of group counseling with video media in reducing menarche anxiety in adolescents in Tanjung Atap Village. This study uses a quantitative approach with a quasi-experimental type of research with Non-Equivalent Control Group Design, the research subjects were 14 people who were taken by purposive sampling technique, the instrument used was adopted from the menarche anxiety questionnaire by Nazariana. The data analysis technique used a paired sample test. t-test. The results of this study show that group counseling using video media is effective in reducing menarche anxiety, t = 21,174 with M M = 128.67, while after treatment the anxiety level of adolescent menarche is in the low category with M = 88.00. Group counseling with media video effective to reduce menarche.